2023
DOI: 10.1088/1402-4896/ace566
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-mediated modulation of morphology and charge transfer dynamics in tungsten oxide nanoparticles

Abstract: Tungsten Oxide (WO3) is a well-known transition metal oxide which exhibits non-toxicity and stability in its nanoparticle form. It is a potential candidate for a variety of applications due to its low cost and facile synthesis process. In the present work, WO3 nanoparticles were synthesized via facile acid-coprecipitation method to explore the effect of surfactants on the morphology of WO3 nanoparticles and thus, on its structural, optical and electrochemical properties. The morphology analysis revealed the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 35 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Moreover, a few TMOs show excellent photocatalytic properties enabling the generation of electron–hole pairs. An excellent TMO with a number of intriguing characteristics is tungsten oxide (WO 3 ). The exceptional properties of WO 3 as discussed in our earlier works , make it a versatile material for a variety of applications.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, a few TMOs show excellent photocatalytic properties enabling the generation of electron–hole pairs. An excellent TMO with a number of intriguing characteristics is tungsten oxide (WO 3 ). The exceptional properties of WO 3 as discussed in our earlier works , make it a versatile material for a variety of applications.…”
Section: Introductionmentioning
confidence: 81%
“…reported a vertical heterostructure formed by monolayer CVD-grown MoS 2 and WO 3 films. , The morphology of the particles depends on the synthesis technique employed and the parameters used during the synthesis. Kumar et al reported the synthesis of WO 3 nanostructures via facile acid coprecipitation method which we have used in the present work for the preparation of nanocomposites owing to the advantages of this methods as reported by Kumar et al Most of the previous research has primarily focused on applications related to wastewater management, water splitting and gas sensors. The composite structures have previously shown excellent photocatalytic activity, permit effective charge separation, and encourage light absorption across a wider spectrum …”
Section: Introductionmentioning
confidence: 90%
“…The presence of Warburg impedance confirms that the exchange of ions between the electrolyte and thin film is happening at a higher rate creating a infinite layer of electron on the surface of thin film. The plot for CSD shown in figure 10(a) suggests that CSD is a potential candidate for solar cell applications but it cannot be used in such applications The Bode plots of the as synthesized samples have also been plotted which exhibits the change in impedance and phase angle with log frequency [63]. The Bode plot shows stability in system setup.…”
Section: Peismentioning
confidence: 99%
“…T W-H plots [as shown in figures 4(a) and (b)] are obtained taking βcosθ and 4sinθ as y and x-axis respectively. The slope of the plot gives the value of the strain present in the as-synthesized samples, whereas intercept of these plots is used to estimate the crystallite size of the samples following eqution-5 [44].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Figure 12(a) depicts the Nyquist plot for hexagonal ZnS. The PEIS system is operated in a frequency range of 7 MHz to 10 mHz [44,58]. The system shows high gain margin as the system remains stable for both higher and lower frequency range.…”
Section: Potentio Electrochemical Impedance Spectroscopy (Peis)mentioning
confidence: 99%